2020
DOI: 10.1177/0891988720957104
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mindfulness-Based Interventions for Patients with Mild Cognitive Impairment or Dementia and Caregivers

Abstract: The aim of this article was to systematically review the quality and efficacy of the current evidence for mindfulness-based interventions (MBIs) in patients with mild cognitive impairment (MCI), patients with dementia (PwD), and their caregivers. We identified 20 randomized controlled trials (RCTs) (11 for patients, 9 for caregivers) published in the last 15 years. Evidence suggested that MBIs are highly acceptable and credible treatments for patients with MCI, PwD and caregivers. Specifically, for PwD, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 106 publications
1
27
1
2
Order By: Relevance
“…Smaller pilot studies have generally not found positive effects 28,29 . In a two-year trial, Quintana-Hernández, Miró- Overall, the literature of using MBIs to combat cognitive decline in the early stages of dementia is highly mixed, comprising small effects that are heterogeneous across cognitive domains 15 . Consistent with this pattern, we did not observe a clear benefit of MBI over TAU, even though the treatment was effective in improving global cognition (MMSE scores) and superior to CRT in improving delayed memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller pilot studies have generally not found positive effects 28,29 . In a two-year trial, Quintana-Hernández, Miró- Overall, the literature of using MBIs to combat cognitive decline in the early stages of dementia is highly mixed, comprising small effects that are heterogeneous across cognitive domains 15 . Consistent with this pattern, we did not observe a clear benefit of MBI over TAU, even though the treatment was effective in improving global cognition (MMSE scores) and superior to CRT in improving delayed memory.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently some evidence that MBIs can slow or reverse cognitive decline in persons with neurodegenerative disorders, [11][12][13][14] with a recent systematic review suggesting that effect sizes are in the small-to-medium range. 15 In particular, it has been suggested that early intervention, such as at the stage of mild cognitive impairment (MCI), is more effective than when patients progress to more severe disease. MCI is a transitional state between normal aging and very early dementia marked by progressive cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, given the limitations public health measures place on the provision of in-person supports, service providers are encouraged to consider alternative psychosocial interventions to strengthen caregiver well-being. For example, preliminary evidence suggests that mindfulness-based interventions (e.g., sitting/walking meditation, deep breathing, mindful movement, and visualization) have the potential to reduce stress, depressive symptoms, and anger and improve self-efficacy and quality of life over the short-term ( Liu et al, 2017 ; Shim et al, 2021 ). Similarly, cognitive behavioral therapy interventions that focus on cognitive-reappraisal techniques, and self-care practices ( Wiegelmann et al, 2021 ), and individual counseling sessions and telephone counseling at monthly intervals ( Phung et al, 2013 ; Tremont et al, 2015 ) have also been shown to promote caregiver mental health through the reduction of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This RCT thus filled the gap in the literature for a robust and rigorously conducted RCT with the inclusion of an active control group to determine the effectiveness of a mindfulness intervention with older adults clinically diagnosed with MCI [ 51 ]. In particular, this study contributes to addressing the scarcity in the literature on mindfulness intervention focusing on an array of multiple cognitive abilities and diverse peripheral biomarkers in older adults with MCI, utilizing parallel-group RCT design, which is conducted with an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous studies [ 35 , 49 , 50 , 51 ] examining the effects of mindfulness on the means and SDs for co-primary outcomes chosen for this study, i.e., fluid biomarkers and neurocognitive tests, we estimated the effect sizes to be 0.5. Hence, we required 24 participants in each group to have a power of 80% to detect statistical significance at 5% level.…”
Section: Methods and Designmentioning
confidence: 99%